1997
DOI: 10.1097/00001756-199702100-00037
|View full text |Cite
|
Sign up to set email alerts
|

Increased dopamine activity associated with stuttering

Abstract: Position emission tomography using 6-FDOPA as a marker of presynaptic dopaminergic activity was used to investigate the role of the dopamine system in stuttering. Three patients with moderate to severe developmental stuttering were compared with six normal controls. Stuttering subjects showed significantly higher 6-FDOPA uptake than normal controls in medial prefrontal cortex, deep orbital cortex, insular cortex, extended amygdala, auditory cortex and caudate tail. Elevated 6-FDOPA uptake in ventral limbic cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
123
0
7

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(137 citation statements)
references
References 7 publications
7
123
0
7
Order By: Relevance
“…In this study, patients have a significantly higher CC genotype (P¼0.001) and lower CT genotype (P¼0.006) when compared with the controls, which is compatible with an earlier result in which stuttering patients showed a large increase in dopamine activation in the presynaptic area. 9 Among the haplotypes of the DRD2 gene, the frequency of 939T/957T is significantly lower in the patient group (P¼0.001; OR¼0.001, 95% confidence interval 0.000-0.010), indicating its protective effect on disorders of fluent speech in the Han Chinese. The results showed that the highest association is observed between rs6277 in the DRD2 gene and disorders of fluent speech.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this study, patients have a significantly higher CC genotype (P¼0.001) and lower CT genotype (P¼0.006) when compared with the controls, which is compatible with an earlier result in which stuttering patients showed a large increase in dopamine activation in the presynaptic area. 9 Among the haplotypes of the DRD2 gene, the frequency of 939T/957T is significantly lower in the patient group (P¼0.001; OR¼0.001, 95% confidence interval 0.000-0.010), indicating its protective effect on disorders of fluent speech in the Han Chinese. The results showed that the highest association is observed between rs6277 in the DRD2 gene and disorders of fluent speech.…”
Section: Discussionmentioning
confidence: 97%
“…6 The dopamine excess theory of stuttering suggests that stuttering may be related to excess levels of the neurotransmitter in the brain. [7][8][9] Further evidence for the theory came from attempts at treating stuttering with antipsychotic medications that block dopamine in the brain. [10][11][12][13] A study to evaluate the efficacy of risperidone in the treatment of developmental stuttering showed that a significant decrease of stuttering severity occurred in the risperidone treatment group than in that of the placebo group.…”
Section: Introductionmentioning
confidence: 99%
“…Wu ve ark. tarafından kekemelik etiyolojisine yönelik yapılan çalışmada striatumdaki hipometabolizmanın dopamin yüksekliğinden kaynaklandığı PET görüntülemeleri ile de desteklenmiştir (12).…”
Section: Discussionunclassified
“…Bir Paradoks Olarak Risperidon Kullanımına Bağlı Kekemelik Olgu Antipsikotikler hem psikiyatrik hastalıkların tedavisinde hem de kekemelik tedavisinde kullanılmaktadır. Psikostimülan tedavi alanlarda dopamin aktivitesinin artmasına bağlı olarak kekemelik ortaya çıkması, ayrıca gelişimsel kekemeliği olan olgulara levodopa gibi dopamin agonistlerinin verilmesi sonucunda kekemeliklerinin kötüleşmesi ve kekemelerde serebral dopamin aktivitesindeki anormal artışın saptanması, kekemelik tedavisinde antipsikotik kullanımı açısından yol gösterici olmuştur (10,11,12).…”
Section: Introductionunclassified
“…Recent studies demonstrate a higher prevalence of stuttering in ADHD patients compared to the general population (6,7,9). These findings indicate that the co-existence of ADHD and stuttering should not be overlooked.…”
mentioning
confidence: 88%